KENTONGAN DAN SIMBOL STATUS SOSIAL: STUDI KASUS DI WILAYAH DESA PAKETINGAN KECAMATAN SAMPANG KABUPATEN CILACAP - teguh hindarto (UNIVERSITAS SEBELAS MARET (UNS), 2018)
Kentongan, not just a product of culture, has an intrumental function, one of which is a tool of communication among traditional communities by using certain tones that have been agreed upon and passed on from generation to generation. But for certain groups of people, especially the Paketingan Village, Sampang District, Cilacap Regency, Kentongan has a social function that is a marker of one's social status. Kentongan as a marker of social status is distinguished based on several categories of wood species, wood size, kentongan laying and a number of other categories. Through studies and case studies of Kentongan's social function as a marker of social status, it is hoped that it will enrich our understanding of the existence of kentongan which is not only understood as a product of a culture.Keywords: Kentongan, Social Status, Status SymbolAbstrakKentongan, bukan sekedar produk sebuah kebudayaan memiliki fungsi intrumental yang salah satunya sebagai alat berkomunikasi di kalangan masyarakat tradisional dengan menggunakan nada-nada tertentu yang telah disepakati dan diteruskan dari generasi ke generasi. Namun bagi kalangan masyarakat tertentu khususnya Desa Paketingan, Kecamatan Sampang, Kabupaten Cilacap, kentongan memiliki fungsi sosial yaitu sebagai penanda status sosial seseorang. Kentongan sebagai penanda status sosial dibedakan berdasarkan beberapa kategori baik jenis kayu, ukuran kayu, peletakkan kentongan dan sejumlah kategori lainnya. Melalui kajian dan studi kasus mengenai fungsi sosial kentongan sebagai penanda status sosial, diharapkan memperkaya pemahaman kita mengenai keberadaan kentongan yang tidak sekedar dipahami sebagai benda produk sebuah kebudayaan.Kata Kunci: Kentongan, Status Sosial, Simbol Status